Numerical and analytical investigation on a multilayer water façade system subjected to blast loading. (15th December 2016) - Wang, Yonghui; Liew, J.Y. Richard; Zhai, Ximei; Wang, Wei; Lee, Siew Chin
Abstract: A novel multilayer façade system, which consisted of a water steel tank integrated with a layer of energy absorbing aluminum foam panel and a stiffened steel panel, was developed to resist blast loading. The blast resistance and response behavior of the proposed façade system were investigated using nonlinear finite element method. The accuracy of the numerical model was verified by comparing the predicted results with the test results. The analyses showed that the energy absorbing aluminum foam layer was capable of reducing the blast load acting on the façade panel and building. The blast resistance of the multilayer façade system could be further enhanced by increasing the aluminum foam layer thickness. An analytical model considering Dynamic Increase Factor (DIF) and coupled deflection mode shapes was developed to predict the displacement response of the façade system subjected to blast loading. The accuracy of the analytical model was validated by comparing the predicted results with the numerical results. It was found that the analytical model with varying DIF could provide better prediction of the displacement response of the multilayer water façade system as compared to the method using a constant DIF.